Design Principles and Applications of Virtual Telepresence Robots: A Comprehensive Review - Navneet Kaur; Palak Katare; Tanu Vishwakarma; Vartika Bhujbal; Ragini Kushwaha (International Journal of Advanced Control and System Engineering, 2024)
The primary objective of this project is to develop an advanced virtual telepresence robot system that facilitates remote communication and collaboration in various environments. Through the integration of cutting-edge robotics, sensing, and communication technologies, our virtual telepresence robot enables real-time interaction between users located at different physical locations. This technology combines wireless connectivity, robotics, and user interfaces to provide people with an immersive experience. This study explores the development, functionality, applications, and future possibilities of virtual telepresence robots. By leveraging the power of interconnected devices and real-time communication, our system contributes to the evolution of telepresence technology, offering new possibilities for remote interaction and engagement in the digital age. The system aims to enhance human presence and engagement in remote scenarios, offering a seamless platform for individuals to interact and collaborate irrespective of geographical constraints. We hope to demonstrate how this technology is changing several industries, such as healthcare, education, business, and personal communication, through a thorough analysis. With the advancement of technology, virtual telepresence robots represent a significant innovation in remote communication and collaboration. Robots that simulate telepresence are transforming remote communication by allowing people to be physically present in far-off places without being there.
Keywords: Bluetooth; NodeMCU; Raspberry Pi; Wi-Fi technology; remote communication; technology; telepresence robots